The Yankee Sphinx : an FDR novel - Frost, Mark, 1953- (Flatiron Books, 2026)
"An extraordinary work of historical fiction by the cocreator of Twin Peaks-a novel about one of FDR's closest wartime advisers and the president's final days, inspired by the author's own family In 1934, Will Hassett is working as a journalist when he gets a call from an old friend who now works at the White House. He arrives expecting to catch up on old times but is instead brought right into the Oval Office to meet with Franklin D. Roosevelt. FDR needs help on his speeches; Will takes the job on the spot. For the next twelve years, Will is at FDR's side through the worst of the Depression, three reelection campaigns, and World War II. The Yankee Sphinx, inspired by Will Hassett's real diaries, focuses on the last few years of FDR's life. The war is raging in Europe and FDR's good friend, Winston Churchill, begs for America's help. But Roosevelt knows he can't bring the country in until it's ready, an opportunity that won't arise until the Japanese attack Pearl Harbor in 1941. From Will's empathetic perspective, we witness FDR managing the Allied military campaign abroad and parrying shots from isolationist politicians at home-all while reckoning with his rapidly deteriorating health. Will and Anna, Roosevelt's daughter, plot an intervention to get him a doctor more up to speed on a new discipline called "cardiology" so the president can maintain his strength and end the war. Elegantly written, bursting with personality, and perfectly capturing life in wartime Washington, The Yankee Sphinx is a marvelous work by one of our most versatile writers"-- Provided by publisher.